Is the Frequency Content of the Calls in North American Treefrogs Limited by Their Larynges?. (23rd September 2014) - Gridi-Papp, Marcos
Abstract : A high diversity of mating calls is found among frogs. The calls of most species, however, are simple, in comparison to those of mammals and birds. In order to determine if the mechanics of the larynx could explain the simplicity of treefrog calls, the larynges of euthanized males were activated with airflow. Laryngeal airflow, sound frequency, and sound intensity showed a positive direct relationship with the driving air pressure. While the natural calls of the studied species exhibit minimal frequency modulation, their larynges produced about an octave of frequency modulation in response to varying pulmonary pressure. Natural advertisement calls are produced near the higher extreme of frequency obtained in the laboratory and at a slightly higher intensity (6 dB). Natural calls also exhibit fewer harmonics than artificial ones, because the larynges were activated with the mouth of the animal open. The results revealed that treefrog larynges allow them to produce calls spanning a much greater range of frequencies than observed in nature; therefore, the simplicity of the calls is not due to a limited frequency range of laryngeal output. Low frequencies are produced at low intensities, however, and this could explain why treefrogs concentrate their calling at the high frequencies.